Daya Tarik Iklan dan Kredibilitas Park Hyung Sik Terhadap Produk Avoskin - Amani, Fadhila; Afriani, Anindita Lintangdesi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
The development of information and communication technology has given rise to new cultures that are starting to be recognized by the public. One of them is the Korean Wave phenomenon. Currently, many local beauty and facial care brands are utilizing this Korean Wave phenomenon by releasing advertisements starring Korean artists as celebrity endorsers on social media. One is Avoskin, which released an ad with celebrity endorser Park Hyung Sik on Instagram @avoskinbeauty. This study aims to determine whether there is an influence of advertising appeal (X1) and the credibility of celebrity endorser Park Hyung Sik (X2) on purchase intention in Avoskin products (Y) and how much it affects. The theory used is the Cognitive Response Theory by George E. Belch and Michael E. Belch. This research method is a survey method with an explanatory-type quantitative approach. The population in this study were followers of the @avoskinbeauty Instagram account, with a sample size of 100 people. This research uses nonprobability sampling with a purposive sampling method. Advertising appeal and the credibility of celebrity endorser Park Hyung Sik have a significant effect on purchase intention in Avoskin products, which is 74 percent while the remaining 26 percent.